Adding complexity to complexity: gene family evolution in polyploids - Mable, Barbara; Kiefer, Christiane; Ruiz Duarte, Paola (Frontiers in Ecology and Evolution, 2018)
Comparative genomics of non-model organisms has resurrected whole genome duplication from being viewed as a somewhat obscure process that happens in plants to a primary driver of eukaryotic diversification. The shadow of past ploidy increases has left a strong signature of duplicated genes organized into gene families, even in small genomes that have undergone effectively complete rediploidization. Nevertheless, despite continually advancing technologies and bioinformatics pipelines, resolving the fate of duplicate genes remains a substantial challenge. For example, many important recognition processes are driven not only by allelic expansion through retention of duplicates but also by diversification and copy number variation. This creates technical difficulties with assembly to reference genomes and accurate interpretation of homology. Thus, relatively little is known about the impacts of recent polyploidization and hybridization on the evolution of gene families under selective forces that maintain diversity, such as balancing selection. Here we use a complex of species and ploidy levels in the genus Arabidopsis (A. lyrata and A. arenosa) as a model to investigate the evolutionary dynamics of a large and complicated gene family known to be under strong balancing selection: the S-related kinases, which include the female component of genetically controlled self-incompatibility. Specifically, we question: 1) How does diversity of S-related kinase (SRK) alleles in tetraploids compare to that in their close diploid relatives? 2) Is there increased trans-specific polymorphism (i.e. sharing of alleles that transcend speciation, characteristic of balancing selection) in tetraploids compared to diploids due to the higher number of copies they carry? 3) Do these highly variable loci show evidence of introgression among extant species/ploidy levels within or outside known zones of hybridization? 4) Is there evidence for copy number variation among paralogs? We use this example to highlight specific issues to consider when interpreting gene family evolution, particularly in relation to polyploids but also more generally in diploids. We conclude with recommendations for strategies to address the challenges of resolving such complex loci in the future, using advances in deep sequencing approaches.
Gesehen am 07.08.2019